2005
DOI: 10.1021/ac048178h
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Isotope Composition of Basalt Glass Reference Material

Abstract: We present data on the lithium isotope compositions of glass reference materials from the United States Geological Survey (USGS) and the National Institute of Standards and Technology (NIST) determined by multicollector inductively coupled plasma mass spectrometry (MC-ICPMS), thermal ionization mass spectrometry (TIMS), and secondary ionization mass spectrometry (SIMS). Our data on the USGS basaltic glass standards agree within 2 per thousand, independent of the sample matrix or Li concentration. For SIMS anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(113 citation statements)
references
References 33 publications
10
103
0
Order By: Relevance
“…Copper has two stable isotopes, 63 Cu and 65 Cu, with isotopic abundances of 69.2 and 30.8 %, respectively, in naturally occurring terrestrial material. Isotopic variations are measured relative to NIST SRM 976 and reported as δ 65 Cu SRM976 values.…”
Section: /58mentioning
confidence: 99%
See 1 more Smart Citation
“…Copper has two stable isotopes, 63 Cu and 65 Cu, with isotopic abundances of 69.2 and 30.8 %, respectively, in naturally occurring terrestrial material. Isotopic variations are measured relative to NIST SRM 976 and reported as δ 65 Cu SRM976 values.…”
Section: /58mentioning
confidence: 99%
“…Isotopic variations are measured relative to NIST SRM 976 and reported as δ 65 Cu SRM976 values. Natural samples cover a range of roughly 16 ‰ with the most positive values found in carbonates and the most negative values in copper chlorides [32].…”
Section: /58mentioning
confidence: 99%
“…Triton thermal ionization mass spectrometer (TIMS) at the University of Bristol, following 215 the method of Kasemann et al (2005). The Li concentration of the spike was calibrated 216 against a gravimetric solution of the NIST Li isotope standard, SRM 8545 (L-SVEC).…”
Section: Determination Of LI Concentration By Isotope Dilution 210mentioning
confidence: 99%
“…12.173 (Flesch et al, 1973), and the reported ratios of 12.568 and 12.553 (Kasemann et al, 2005) were taken for NIST 610 and NIST 612, respectively.…”
Section: Accepted Manuscriptmentioning
confidence: 99%